The Feasibility of Transitioning Low-density Suburbs into Healthy Walkable Neighbourhoods: The Case of Adelaide, South Australia. Issue 4 (2nd October 2021) - McGreevy, Michael; Musolino, Connie; Udell, Tuesday; Baum, Fran
ABSTRACT: Research has demonstrated that there are health and equity benefits attached to residing in neighbourhoods with the design, diversity and density required for walkability. Research has tended to show that the very low residential densities found in Australian suburbs are major obstacles to retrofitting walkability. We undertook a survey of 27 neighbourhoods and their activity centres in Adelaide, South Australia to ascertain the minimum residential densities required to make a diverse activity centre viable. The findings suggest that retrofitting established suburbs with the design and viable destinations required to substantially improve walkability does not require large increases in residential density.